AMPLIFIKASI GEN 16S-rRNA BAKTERI TERMOFILIK DARI SUMBER AIR PANAS, GUNUNG PANCAR BOGOR - Suryani -; Laksmi Ambarsari; Efi Sanfitri Harahap (Jurnal Riset Kimia, 2009)
ABSTRACT Exploration of thermophilic bacteria that produce thermostable enzyme is most useful in application for enzyme base industrial. The aim of of this research is to isolate and amplificate the 16S-rRNA gene from thermophilic bacteria isolate at hotspring, Mount of Pancar, Bogor. The research steps consist of bacteria isolation, chromosomal DNA extraction, and amplification of 16S-rRNA gene. The water sample as source for bacteria was collected from four cauldrons. Temperature and pH for each cauldron are red cauldron 75-80°C, pH 7; black cauldron 55°C, pH 7; white cauldron 57°C, pH 7; and saline cauldron 25°C, pH 6, respectively. The bacteria were cultivated at Luria Bertani (LB) and Thermus media. The chromosomal DNA have been extracted. Gene amplification of 16 S-rRNA have been carried out by using universal primer (Bac F1 and Uni B1). The size of amplicon is ± 1.5kb. Keywords : thermophilic bacteria, chromosomal DNA extraction, amplification of 16S-rRNA gene